If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 2(-3x + -7) = -21 + -2x Reorder the terms: -3x + 2(-7 + -3x) = -21 + -2x -3x + (-7 * 2 + -3x * 2) = -21 + -2x -3x + (-14 + -6x) = -21 + -2x Reorder the terms: -14 + -3x + -6x = -21 + -2x Combine like terms: -3x + -6x = -9x -14 + -9x = -21 + -2x Solving -14 + -9x = -21 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -14 + -9x + 2x = -21 + -2x + 2x Combine like terms: -9x + 2x = -7x -14 + -7x = -21 + -2x + 2x Combine like terms: -2x + 2x = 0 -14 + -7x = -21 + 0 -14 + -7x = -21 Add '14' to each side of the equation. -14 + 14 + -7x = -21 + 14 Combine like terms: -14 + 14 = 0 0 + -7x = -21 + 14 -7x = -21 + 14 Combine like terms: -21 + 14 = -7 -7x = -7 Divide each side by '-7'. x = 1 Simplifying x = 1
| 10a-5=7a-2 | | 5x-4=x+12 | | 16x-82=116+7x | | 6a+13=27+3a | | 4x+2=3x^2 | | 4m-11=7m-13 | | 6-5t=9-2t | | 6a+9=2a-7 | | 3(-8)+(7(-8))= | | 20x-13(2.923076923)=-35 | | 4y+10=7y-2 | | 11a+3=9a+1 | | 8t+11=7t-4 | | w^2=-6-5w | | 6a-13=9a-15 | | 5(49-28z+4x^2)=0 | | -4x-(-3x)-5-(-6x)-8=0 | | 64b^2-25d^2=0 | | 3(x-5)+7x=5x-25 | | -2x^6-8x^5+64x^4=0 | | -4(2x-3)-2x=-8 | | 2xx+2x+2=0 | | 11x-4-6x=3x+10 | | 6x+5=3x+11 | | 5(x-4)+x=16 | | 15m^2=76m-5 | | -19+6-(-9)-10+18= | | -10x+3=-3x+24 | | 5x+3=27 | | 8x-19=-3 | | 7x-15=3x+1 | | n+s=926 |